2016
DOI: 10.1159/000452166
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Repair Outcomes of Vesicovaginal Fistula: A Retrospective Review of 139 Procedures

Abstract: Introduction: We aimed to report the outcomes of patients undergoing vesicovaginal fistula (VVF) repair to identify prognostic factors. Materials and Methods: Patients who underwent VVF repair between January 2009 and October 2015 were reviewed. Primary outcome was fistula closure at 3 months. Results: A total of 123 patients and 139 procedures of VVF repair were reviewed. The overall success rate was 85.6%. There were no significant differences in age (p = 0.476), etiology (p = 0.900), fistula duration (p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…Further, it was reported that large size of Þ stula is more likely to be repaired unsuccessfully. 15,16 However, according to our data analysis, no association was observed between preoperative size of Þ stula and successful surgical repair. Similarly, route of repair (vaginal/ abdominal) has insigniÞ cant effect on the outcome of repair.…”
Section: Discussionmentioning
confidence: 52%
“…Further, it was reported that large size of Þ stula is more likely to be repaired unsuccessfully. 15,16 However, according to our data analysis, no association was observed between preoperative size of Þ stula and successful surgical repair. Similarly, route of repair (vaginal/ abdominal) has insigniÞ cant effect on the outcome of repair.…”
Section: Discussionmentioning
confidence: 52%
“…Rectovesical and vesicovaginal fistulas can complicate the course of illness in patients with cancer. They may result from chemotherapy, radiation damage, malignant tumor invasion, and pelvic surgery complications [ 59 , 60 ]. Although these fistulas are infrequently life-threatening, they substantially reduce the patient's quality of life [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these fistulas are infrequently life-threatening, they substantially reduce the patient's quality of life [ 61 , 62 ]. Vesicovaginal fistulas, abnormal connections between the vagina and bladder, usually present with urinary leakage through the vagina, bleeding, and localized pain [ 59 , 60 ]. Because most are caused by invasive tumors, surgical repair is the preferred treatment approach [ 61 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a randomized study of VVF repair comparing both approaches with or without interpositional flap found equivalent results [7]. So both approaches appear to provide comparable outcome with final discretion depending on the surgeon's experience and training [11].…”
Section: Discussionmentioning
confidence: 99%